The Role of Arabic Learning Applications in Teaching and Everyday Use: An Analytical Study: Peran Aplikasi Pembelajaran Bahasa Arab dalam Pengajaran dan Penggunaan Sehari-hari: Sebuah Studi Analitis - Bousnane, Rokia (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2025)
The research addressed an important aspect of modern technology in teaching the Arabic language and facilitating its use for all groups that rely on it. This aspect is represented in the Arabic language applications available on smartphones. This is a new study that lacks previous literature, to the best of the researcher's knowledge. The research aims to: 1) Identify the advantages of Arabic language applications on smartphones; 2) Identify the characteristics of Arabic language applications on smartphones; 3) Clarify the obstacles facing Arabic language applications in contributing to its teaching and facilitating its use; 4) Identify the technical and scientific standards that serve the Arabic language through smartphone applications; 5) Identify the quality aspects of Arabic language applications on smartphones. The research used the content analysis method, which focused on classifying the content of applications into content categories and problem categories. It reached important results, including: Many Arabic language and science applications on smartphones provide many functions, represented by educational functions, advisory functions, and constructive functions. Arabic language and science applications are characterized by organized and diverse content that includes grammar, syntax, explanation of meanings, and facilitation of letter writing and pronunciation. Some Arabic language and science apps suffer from several problems, such as accompanying ads and difficulty dealing with complex ads. Keywords: Apps, Smartphones, Arabic, Education, Standards.